Food Diversification of Cassava as Functional Food Instead of Rice in Lampung - Arief, Ratna Wylis; Novitasari, Erliana; Asnawi, Robet (Universitas Muhammadiyah Yogyakarta, 2018)
Cassava has been known to have low glycaemic index (GI) recommended for diabetics. Cassava can be used as alternative food source for substitution of rice as Indonesian staple food. The current study aimed to investigate phisycal and chemical properties of food diversification of cassava. Levels of dietary fibre were measured by enzymatic-gravimetric AOAC, while total sugar content was measured by Lane-Eynon titration. Determination of starch was observed by using spectrophotometer and energy analysis by bomb calorimetry. Level of glycaemic index (GI) was determined by EL, S.N. method. The sensory analysis was performed by preference test by using hedonic scale towards 20 panelists. Analysis of cost and benefit was used to investigate the economic feasibility of the products. Among several products of cassava, analog rice has the highest value of dietary fibre (4.72%), starch (75.64%) and energy level (349.38 cal/kg). In addition, it has the lowest value of total sugar content (1,19%) and GI (56). It is also the most preferable in terms of colour (4.35), aroma (3.90), taste (4.35) and general acceptance (4.05). Economically, analog rice provides the highest profit than instant tiwul and oyek, which are 1.66; 1.56 and 1.47 respectively.